Physiotherapeutic treatment after break and reconstruction of ACL - Dominiak, Adrian; Wrzesiński, Bartłomiej; Piechocka, Edyta; Wojtczak, Paweł; Ziółkowska, Anna; Śniegowska, Wiktoria; Ciecierska, Dominika; Bielejewska, Marta (Journal of Education, Health and Sport, 2018)
Injuries of the knee joint are amongst the most common diseases that affect the human body. It is estimated that they affect about 15-30% of all body injuries. Beside the lateral ligaments the most the structure exposed for the any kind of damage is ACL. Concerning the cruciate ligaments, as much as 90% of the injuries are related to ACL [52]. Most often the damage to this structure occurs when practicing sports, both contact (for example basketball, football, martial arts) and non-contact like skiing.